Perancangan Sistem Informasi Administrasi Pelayanan Tamu Berbasis Desktop pada Kelurahan Pluit - Hasanah, Riyan Latifahul; Siswandi, Agus (Universitas Multi Data Palembang, 2024)
In the current era of globalization, information technology is developing very rapidly. The need for data and information is needed, especially in the business sector and government agencies. The Pluit Village Office is a government agency that works to serve the community. However, the management of guest data at the Pluit Kelurahan office still uses the manual method and has not even been recorded properly, this causes difficulties in recording and managing guest data and preparing reports. This study aims to design a desktop-based guest service administration information system to assist in the process of managing guest data in Pluit Village. Data collection was carried out by direct observation, interviews and literature study in order to make a systematic and accurate picture of the guest service process at Pluit Village. The method used in this study is the Waterfall method. The application is built using the Visual Basic.Net 2022 programming language and uses the MySQL Database. This research resulted in a computerized guest service administration information system to facilitate storage, data processing and report generation.